AB0126 CD70 Expressing CD4 T Cells Produce IFN-Γ and IL-17 in Rheumatoid Arthritis. (10th June 2014) - Park, J.K.; Han, B.K.; Park, J.A.; Woo, Y.J.; Kim, S.Y.; Lee, E.Y.; Lee, E.B.; Chalan, P.; Boots, A.M.; Song, Y.W.
Abstract : Background: CD70 expressing CD4 T cells are enriched in rheumatoid arthritis (RA) and promote autoimmunity via costimulatory CD70-CD27 interaction. To date, it is unknown whether CD70+ CD4 T cells contribute to RA pathogenesis via other mechanisms than the CD70-CD27 interaction. Objectives: To explore the phenotype and cytokine production of CD70+ CD4 T cells in RA. Methods: Peripheral blood mononuclear cells (PBMCs) from 32 RA patients were isolated and frequencies of CD70+ cells within different CD4 T subsets were analyzed using flow cytometry. Interferon (IFN)-γ and interleukin (IL)-17 production were compared between the CD70+ and CD70- cells. Expression of master transcription factors T-bet, GATA3 and retinoic-acid-related orphan receptor gamma t (RORγt) were examined by real time-PCR. Results were in mean ± standard error of the mean. Results: CD4 T cells of healthy controls rarely expressed CD70 as compared to CD4 T cells of RA patients (0.9±0.3% vs. 7.6±0.6%, p<0.001, panel A). In RA, CD70+ cells were present within all CD4 T cell subsets, i.e. CD45RA+ CCR7+ naïve, CD45RA-CCR7+ central memory, CD45RA-CCR7- effector memory, and CD45RA+ CCR7- terminally differentiated effector memory T cells with a frequency of 3.9±1.1%, 4.0±0.5%, 4.2±0.7%, and 9.4±4.3%, respectively (panel B). As compared to CD70- CD4 T cells, CD70+ CD4 T cells produced significantly more IFN-γ (panel C) and IL-17 (panel D) after short activation. CD70+ CD4 T cells preferentially expressed transcription factor RORγt. Conclusions: CD70+ CD4 T cells are enriched in RA and may directly contribute to RA pathogenesis by producing IFN-γ and IL-17. Targeting CD70+ CD4 T cells might offer new therapeutic opportunities in RA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2780